2008
DOI: 10.1021/jf8016833
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Metabonomic Variation of Rosemary Extracts Using 1H NMR Spectroscopy and Multivariate Data Analysis

Abstract: The molecular compositions of rosemary ( Rosmarinus officinalis L.) extracts and their dependence on extraction solvents, seasons, and drying processes were systematically characterized using NMR spectroscopy and multivariate data analysis. The results showed that the rosemary metabonome was dominated by 33 metabolites including sugars, amino acids, organic acids, polyphenolic acids, and diterpenes, among which quinate, cis-4-glucosyloxycinnamic acid, and 3,4,5-trimethoxyphenylmethanol were found in rosemary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
114
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 31 publications
4
114
0
1
Order By: Relevance
“…Metabolic profiling based on NMR is a fast, convenient, and effective tool for identifying differential metabolites between groups of related (control and exposed) biological samples. In addition, since NMR spectroscopy can simultaneously detect all proton containing metabolites, NMR-based metabolomics has been widely applied in plant sciences (Dai et al 2010;Xiao et al 2008). Metabolomics on the plant usually focuses on the plant-environment interactions and assessment of plant function and health at molecular level (Lindon et al 1999;Aliferis et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic profiling based on NMR is a fast, convenient, and effective tool for identifying differential metabolites between groups of related (control and exposed) biological samples. In addition, since NMR spectroscopy can simultaneously detect all proton containing metabolites, NMR-based metabolomics has been widely applied in plant sciences (Dai et al 2010;Xiao et al 2008). Metabolomics on the plant usually focuses on the plant-environment interactions and assessment of plant function and health at molecular level (Lindon et al 1999;Aliferis et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many new compounds and even trace metabolites have been successfully discovered since the arrival of this technique. For example, recently, the chemical composition of rosemary [23] has been characterized using the combination of 2D NMR of the mixture and the HPLC-DAD-MS-SPE-NMR hyphenated technique. [29] A total of 33 metabolites including sugars, amino acids, organic acids, polyphenolic acids and diterpenes have been identified, in which quinate, cis-4-glucosyloxycinnamic acid and 3,4,5-trimethoxyphenyl-methanol were found in rosemary for the first time.…”
Section: Applicationsmentioning
confidence: 99%
“…[29] A total of 33 metabolites including sugars, amino acids, organic acids, polyphenolic acids and diterpenes have been identified, in which quinate, cis-4-glucosyloxycinnamic acid and 3,4,5-trimethoxyphenyl-methanol were found in rosemary for the first time. [23] Taking quinate as an example, two-dimensional NMR spectra including TOCSY, HSQC and HMBC were acquired from the rosemary extract (mixture). Xiao et al have found [23] a ring structure in TOCSY spectrum (Fig.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esto ha generado que en los últimos años la demanda mundial por estos productos sea creciente, sumado a la diversidad racial y a las preferencias culturales por las comidas condimentadas (Cracker, 2007;Souza et al, 2008;Xiao et al, 2008).…”
Section: Introductionunclassified